Physical performance in paralympic wheelchair rugby athletes from Cundinamarca-Colombia - Diogo, B. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In wheelchair rugby, players use an offensive or defensive wheelchair depending on their position on the field and their level of disability. The performance of wheelchair rugby players is related to several paramenters, degree of disability, physical ability, time of experience, type of wheelchair, which are related to sport performance. The objective of this study is to analyze the physical performance of wheelchair rugby athletes from Cundinamarca-Colombia. METHODS: Eleven people belonging to the wheelchair rugby league of Cundinamarca-Colombia were tested for physical and technical performance, ball handling, blocking performance, 20-meter speed, long-distance passing, Illinois agility test, 40-meter test, up and backs. RESULTS: Age 37.4 (10.2), Peak speeds of the first 2 pushes (acceleration phase) were significantly higher with the defensive wheelchair than with the offensive wheelchair (p < 0.05 and p < 0.03). Mean and peak sprint velocity were significantly greater (p < 0.04 and p < 0.06, respectively) with the defensive wheelchair. In ball handling 8.36 (3.07) sec, blocking performance 29.67 (7.16) effective. CONCLUSION: The performance was lower with the offensive wheelchair than with the defensive one, suggesting the frequent finding that the higher performance of defensive players compared to offensive ones, the technical variables are aperfecioamento elements for a development with more effective in the matches potentiating better performance for wheelchair rugby.